2010
DOI: 10.1111/j.1865-1682.2010.01098.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemorrhagic Diathesis in Neonatal Calves: An Emerging Syndrome in Europe

Abstract: In 2008 and 2009 a large number of cases of haemorrhagic diathesis (HD) in neonatal calves were reported in different European countries. In Flanders, 84 cases of neonatal HD in 30 herds were reported in this period. The disease typically affects calves younger than 1 month old from different breed and gender. Prominent clinical signs are cutaneous bleeding, petechiae on all mucosae, melena and often high fever. Early in the disease, the mental state of the animals is uncompromised. The typical haematological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 28 publications
(32 reference statements)
2
60
0
1
Order By: Relevance
“…calves has been reported in several European countries (1)(2)(3)(4) and has been designated as bovine neonatal pancytopenia (BNP). The disease is characterized by severe thrombocytopenia and leukopenia-essentially a strong neutropenia and a mild lymphopenia-in 2-to 3-wk-old calves and in most cases leads to hemorrhages and a fatal issue.…”
Section: S Ince 2007 An Emergent Life-threatening Disease Of Neonatalmentioning
confidence: 99%
“…calves has been reported in several European countries (1)(2)(3)(4) and has been designated as bovine neonatal pancytopenia (BNP). The disease is characterized by severe thrombocytopenia and leukopenia-essentially a strong neutropenia and a mild lymphopenia-in 2-to 3-wk-old calves and in most cases leads to hemorrhages and a fatal issue.…”
Section: S Ince 2007 An Emergent Life-threatening Disease Of Neonatalmentioning
confidence: 99%
“…Hematology from BNP cases reveals a profound thrombocytopenia and leukopenia [2,13] and histopathology of bone marrow shows extensive depletion of hematopoietic cells (Figure 1). Experimental studies reproducing the disease demonstrated that as early as 4 h following ingestion of alloantibodies there is already a 75-95% reduction in peripheral blood lymphocytes, monocytes and neutrophils [16,17].…”
Section: Clinical Signs and Pathology Of Bnpmentioning
confidence: 99%
“…Rapid internal bleeding can result in affected calves being found dead with no external signs of hemorrhage, contributing to the under-reporting of cases [4]. Intercurrent infections are common and often result in profound pyrexia [2,13,15]. The majority (80-90%) of clinically affected calves die or are euthanized soon after the onset of symptoms [2,13], however in some cases recovery from the condition is possible [2,13].…”
Section: Clinical Signs and Pathology Of Bnpmentioning
confidence: 99%
See 2 more Smart Citations